The changing public sphere on Twitter: Network structure, elites and topics of the #righttobeforgotten. (December 2017) - Yang, Shuzhe; Quan-Haase, Anabel; Rannenberg, Kai
Since the ruling of the European Court of Justice, the right to be forgotten has provided more informational self-determination to users, whilst raising new questions around Google's role as arbiter of online content and the power to rewrite history. We investigated the debate that unfolded on Twitter around the #righttobeforgotten through social network analysis. The results revealed that latent topics, namely Google's role as authority, alternated in popularity with rising and fading flare topics. The public sphere, or Öffentlichkeit, that we observed resembles the traditional one, with elite players such as news portals, experts and corporations participating, but it also differs significantly in terms of the underlying mechanisms and means of information diffusion. Experts are critical to comment, relay and make sense of information. We discuss the implications for theories of the public sphere and examine why social media do not serve as a democratising tool for ordinary citizens.